STRENGTHENING STUDENTS' CRITICAL REASONING CHARACTER IN PAI LEARNING: CONTEXT OF IMPLEMENTING THE INDEPENDENT LEARNING CURRICULUM - Nurhayati, R; Umar, Umar; Takdir, Takdir; P, Sudirman; Ningsih, Diarti Andra; Usman, M Nurkhaliq; Usman, M Nurkhaliq; Nurlina, Nurlina; Triandana, Jenita (Proceeding of International Conference on Islamic Education (ICIED); Vol 8 No 1 (2023): Proceeding of International Conference on Islamic Education (ICIED), 2023)
This research aims to explore and analyze the implementation of the Independent Learning Curriculum in forming critical reasoning character in PAI learning. This research uses the library research research method, with a descriptive qualitative approach. This research was carried out by exploring documents (libraries) in the form of books, notes or reports of previous research results. The research results show that the implementation of the Merdeka Belajar Curriculum is effective in forming critical reasoning character in PAI learning where the Merdeka Belajar Curriculum provides a learning environment that is more inclusive and student-centered. Through this approach, students are encouraged to become active subjects in the learning process, which helps them develop critical, analytical and reflective thinking skills. Apart from that, in PAI learning, students are invited to link religious values with real life contexts, thereby strengthening the link between theory and practice in building critical reasoning character. The Merdeka Belajar curriculum also emphasizes the importance of using a variety of learning resources, including information and communication technology, to increase students' activeness in seeking information and evaluating various perspectives. This positively contributes to forming a critical reasoning character who is able to understand the complexity of religious and social issues.